Mediální výchova pohledem budoucích učitelů - Janková, Karolina (Univerzita Karlova, Fakulta sociálních věd, 2018)
The aim of this bachelor thesis is to provide a different view on media education, specifically from the point of view of students of the Faculty of Education of Charles University. The thesis provides an insight into the preparation of teachers for their future work in the field, consequently their readiness to teach the subject of Media Education, defined by common frameworks for education created by the Ministry of Education, Youth and Sports. The theoretical background described in the first chapter of the paper provides a basic overview of elementary concepts related to media education and media literacy, the second chapter describes the ways in which future teachers can be trained both within and outside the institution of university. The practical part of the thesis is a questionnaire undertaken at the Faculty of Education among students of various departments. The questionnaire examines how the future teachers` education takes place and how they themselves assess their readiness to teach the subject. The main purpose of the thesis is to map and describe the current situation and to create incentives for future teachers so that the media literacy of Czech pupils gradually improves and becomes more effective. Cílem této bakalářské práce je přinést odlišný pohled na problematiku mediální výchovy, a to konkrétně ze strany studentů Pedagogické fakulty Univerzity Karlovy. Práce má poskytnout vhled do přípravy pedagogů na jejich budoucí povolání, potažmo na jejich připravenost k výuce průřezového tématu Mediální výchova, definovaného Rámcovým vzdělávacím programem. Teoretická východiska popsaná v první kapitole práce poskytují základní přehled spojený s vymezením elementárních pojmů týkajících se mediální výchovy a mediální gramotnosti, druhá kapitola popisuje způsoby přípravy budoucích pedagogů v rámci vysokoškolského vzdělávání i mimo školu. Praktickou část práce pak tvoří dotazníkové šetření realizované na Pedagogické fakultě Univerzity Karlovy mezi současnými studenty různých oborů. Dotazníkové šetření poskytuje podklady pro analýzu současného stavu v oblasti vzdělávání budoucích pedagogů. Zjišťuje, jakým způsobem jejich vzdělání probíhá a jak svou připravenost na výuku mediální výchovy sami hodnotí. Hlavním cílem práce je zmapování současného stavu a vytvoření podnětů pro budoucí pedagogy tak, aby docházelo ke kvalitnímu a účinnému zvyšování mediální gramotnosti českých žáků. Katedra mediálních studií Department of Media Studies Faculty of Social Sciences Fakulta sociálních věd